Implementation Of Article 21 Of Corruption Eradication Act on Advocates Performing Their Professional Function - Nurul Hudi (Fakultas Hukum Universitas Hang Tuah, 2019)
The research problem of this study is the implementation of Article 21 of Act No. 31/1999 in conjunction with Act No. 20/ 2001 concerning Corruption Eradication on Lawyers performing their profession as legal advisors. It is due to the fact that it is not allowed to prosecute advocates who perform their profession, given their right to immunity. The method used in this study is normative juridical method, referring to the acts of legal regulation as mentioned in legislation, particularly those related to corruption cases, given the implementation of article 21 of Act 31/ 1999 jo 20/ 2001 that concerns on corruption as crime. Conceptual and legislation approaches are both used. The result shows that the implementation of article 21 that deals with corruption eradication may also be well conducted on which advocates do their role to take action against corruption while performing their profession.